Study on the Effectiveness of Slow-Release Fertilizer Combining Maggot waste and Azospirillum brasilense on the Growth of Choy Sum (Brassica rapa var. parachinensis) - Wijaya, Alvin Bowen; Kusuma, Achmad Fauzi; Pangestu, Clive Nathan; Jocelino, Vincenzio; Akbar, Verga Windi; Ali, Dego Yusa (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2025)
The use of conventional fertilizers is a major contributor to nitrogen leaching in agriculture. The development of Slow-Release Fertilizers (SRF) has garnered increasing attention due to their ability to control nutrient release. However, current SRF formulations still rely on costly and environmentally unfriendly chemical substrates. The application of SRF using organic maggot waste fertilizer combined with the Plant Growth-Promoting Rhizobacteria (PGPR) Azospirillum brasilense shows potential to rival commercial SRF quality. Maggot waste has been shown to contain NPK levels comparable to commercial fertilizers, while A. brasilense has demonstrated the ability to induce plant growth hormones. This study investigates SRF synthesized with varying amounts of maggot waste and A. brasilense suspension, focusing on SRF characteristics and their effect on the growth of choy sum (Brassica rapa var. parachinensis). All SRF treatment groups exhibited high water absorption and sustained nutrient release for up to 30 days, aligning with the choy sum growth period. The synthesized SRF showed the highest compatibility with the Ritger–Peppas kinetic release model (R² > 0.97), indicating a quasi-Fickian diffusion mechanism. However, the combination of SRF and A. brasilense did not significantly enhance plant growth (p > 0.05) in terms of fresh weight, total leaf area, and leaf count. Further research is needed to optimize SRF formulations for more effective and efficient application in agriculture.